Memperkuat Perekonomian Desa Melalui Budidaya Tembakau Di Desa Tejorejo Kabupaten Kendal - Muhammad Ilham Akbar; Selvia Kurniawati; Iffah Nur Hakim; Lailatul Khasanah; Muhammad Alfandi; Eka Fitriyani; Ana Madinatul Ulum (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
Tobacco cultivation in Tejorejo Village is one of the community's main efforts to improve the village economy. This research uses a qualitative descriptive approach to analyze the challenges faced in tobacco cultivation and their impact on the economy of local communities. The challenges found include technical limitations due to climate change which affects the quality and quantity of harvests. Apart from that, fluctuations in tobacco prices on the market which are influenced by external factors such as government policy and global economic conditions also increase the instability of farmers' income. However, tobacco cultivation has a positive impact in encouraging village infrastructure development and attracting investment. Although progress in the tobacco farming sector can encourage rural infrastructure development and attract investment, over-reliance on tobacco as the sole source of income carries major risks, including economic uncertainty and the potential for crop failure which can impact the village economy as a whole.